Architecture of Wireless Vehicle Weight Measurement System for Structural Health Monitoring in Civil Engineering Application - Artur Andrzejczak; Paweł Łęczycki; Michał Wojtera; Piotr Pietrzak; Bartosz Pękosławski; Andrzej Napieralski (International Journal of Distributed Sensor Networks)
The following paper describes architecture of the Wireless Vehicle Weight Measurement System (WVWMS). The challenge was to design a road scale system enabling multipoint vehicle weight with the single network sink. The proposed platform is capable of weight measurement based on electrical strain gauge weight pads and in-node data processing. Communication is wireless, with mesh networking. The developed vehicle weight measurement is one of subsystems applied in the TULCOEMPA project. It is required to cooperate with Structural Health Monitoring and Truck Recognition Systems. Due to the absence of mains line, all installations are powered by Hybrid Power System. The authors propose Energy Harvesting Controller cooperating with both solar panels and wind generators. The controller enables efficient energy harvesting from both power sources as well as monitoring of generated and consumed power levels. Next challenge was a design of vehicle weight data acquisition software architecture. The solution includes application of modern architectural concepts in software design, Representational State Transfer (REST), Model-View-View Model (MVVM) paradigm, and cloud computing. Communication between vehicle weight measurement modules and server application is described.